Guidance Learning For Increase Creativity in Students Learning in Junior High School - Oktariana, Dina; Zainudin, Zainudin; Nova, Reka (IJoCE: Indonesian Journal of Counseling and Education, 2022)
Creativity is one of the provisions stipulated in Government Regulation No. 19 of 2005 on National Education Standards article 19 paragraph 1 (a) which states that the process of learning in the educational unit organized in an interactive, inspiring, fun, challenging, motivating the students to participate actively, and provide enough space for innovation, creativity, and independence in accordance with their talents, interests, and physical and psychological development of learners.. Seeing the importance of creativity in learning problems, then this paper tries to explore the creativity of academic learning around issues including the definition of creativity in learning, the importance of creativity, the characteristics of creativity, and the role of creativity in learning in the development of learners. The general objective of this study is to produce formulation tutoring models that can improve creativity in learning on the learner. then this paper attempts to explore the creativity of academic learning around issues including the definition of creativity in learning, the importance of creativity, the characteristics of creativity, and the role of creativity in learning in the development of learners. The general objective of this study is to produce formulation tutoring models that can improve creativity in learning on the learner. then this paper attempts to explore the creativity of academic learning around issues including the definition of creativity in learning, the importance of creativity, the characteristics of creativity, and the role of creativity in learning in the development of learners. The general objective of this study is to produce formulation tutoring models that can improve creativity in learning on the learner.